2018
DOI: 10.1016/j.immuni.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor ZEB2 Is Required to Maintain the Tissue-Specific Identities of Macrophages

Abstract: SummaryHeterogeneity between different macrophage populations has become a defining feature of this lineage. However, the conserved factors defining macrophages remain largely unknown. The transcription factor ZEB2 is best described for its role in epithelial to mesenchymal transition; however, its role within the immune system is only now being elucidated. We show here that Zeb2 expression is a conserved feature of macrophages. Using Clec4f-cre, Itgax-cre, and Fcgr1-cre mice to target five different macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
198
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 185 publications
(215 citation statements)
references
References 42 publications
6
198
0
Order By: Relevance
“…A broad dysregulation of the AM molecular program was also reported previously for AMs deficient for the transcription factors PPARc (Schneider et al, 2014), Zeb2 (Scott et al, 2018), and Bach2 (Nakamura et al, 2013), although, in the latter case, cell-intrinsic and cell-extrinsic aspects of the changes in the expression program remain to be fully understood (Ebina-Shibuya et al, 2017). Together with this report, these studies highlight a remarkable complexity of the transcription factor network controlling the AM molecular program.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…A broad dysregulation of the AM molecular program was also reported previously for AMs deficient for the transcription factors PPARc (Schneider et al, 2014), Zeb2 (Scott et al, 2018), and Bach2 (Nakamura et al, 2013), although, in the latter case, cell-intrinsic and cell-extrinsic aspects of the changes in the expression program remain to be fully understood (Ebina-Shibuya et al, 2017). Together with this report, these studies highlight a remarkable complexity of the transcription factor network controlling the AM molecular program.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, the unique tissue‐specific identities of macrophage subsets are likely to be controlled by a combinatorial action of multiple transcription factors, some of which may be expressed more broadly than the others. In line with this notion, it was recently reported that the widely expressed transcription factor Zeb2 controls subset‐specific molecular programs in AMs, microglia, Kupffer cells, and splenic and colonic macrophages (Scott et al , ).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…With the advent of new technologies such as single‐cell RNA‐seq (SC‐RNA Seq), a more comprehensive identification of tissue macrophage subsets has been possible. In particular, the transcription factor zinc finger E‐box binding homeobox 2 (ZEB2) was identified as a key determinant of tissue‐specific macrophages in diverse organs including the liver, lung, spleen, brain and colon . In ZEB2‐deficient mice, there was alteration of different tissue‐specific macrophage markers, highlighting the technical difficulty of identifying macrophages within tissues if using limited markers such as CD64 and F4/80.…”
Section: Wound‐healing Macrophage Heterogeneity and Plasticitymentioning
confidence: 99%